2014
DOI: 10.1111/dote.12271
|View full text |Cite
|
Sign up to set email alerts
|

Impact of anthropometric measures and serum leptin on severity of gastroesophageal reflux disease

Abstract: The aim of this prospective study was to evaluate the impact of obesity, determined by different anthropometric measures, on clinical and endoscopic severity of GERD and the relation between serum leptin and clinical and endoscopic severity of GERD in Egyptian patients. The study was carried out at Ain Shams University Hospitals and Theodor Bilharz Research Institute, Cairo, Egypt. A total of 60 patients with clinically and endoscopically evident gastroesophageal reflux disease (GERD) were enrolled in this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 29 publications
0
8
0
1
Order By: Relevance
“…Obesity, particularly the central type with increased leptin levels have been associated with clinically and endoscopically severe GERD. 25 WHR was not associated with GERD among female cases compared with controls, though WC was. It may be that female cases with GERD equally had high HC, as shown by the mean value of HC among cases and controls which was statistically significant (p < 0.05).…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Obesity, particularly the central type with increased leptin levels have been associated with clinically and endoscopically severe GERD. 25 WHR was not associated with GERD among female cases compared with controls, though WC was. It may be that female cases with GERD equally had high HC, as shown by the mean value of HC among cases and controls which was statistically significant (p < 0.05).…”
Section: Discussionmentioning
confidence: 69%
“…18,24 It may thus point to the fact that GERD is evolving among people from Africa, a fact that has been raised among researchers in Kenya. 25 Among people from Africa, few studies have shown an association between central obesity and GERD. A study from Southwest Nigeria reported a weak association between central obesity and GERD.…”
Section: Discussionmentioning
confidence: 99%
“…In obese patients with GERD, leptin, and ObR levels were found to be higher and lower, respectively, than in nonobese patients with GERD [167,168]. Consistent with this finding, leptin resistance in individuals with overweight and obesity is associated with features of GERD, and leptin levels are positively associated with frequent GERD symptoms [169] and with the clinical and endoscopic severity of GERD [170]. The multi-biomarker score derived from multiple parameters, including leptin levels and GERD frequency and duration, can identify patients with Barrett's esophagus [171].…”
Section: Leptinmentioning
confidence: 81%
“…39 Adipokines have also been implicated in GERD. Increased leptin levels have an association with clinical GERD severity, 40 whereas ghrelin levels have an inverse relationship with GERD. 41 The mechanism underpinning the association between obesity and GERD is complex and multifactorial, working in concert, increasing the TPG, and impairing acid clearance from the esophageal lumen.…”
Section: Anatomy and Pathophysiology Of Gerdmentioning
confidence: 99%